Badiou, Kant, and the Materialism of the Idea - Riha, Rado (Filozofski vestnik, 2016)
The departure point of this article is the assumption that Badiou's “philosophy under conditions” succeeds in avoiding the trap of a dialectics of theory and practice, of the objective and subjective precisely to the extent that it operates with the Idea. The Idea introduced by Badiou's philosophy under conditions is considered as a sign of the advent of a new materialism. The central thesis of the present article being that Kant's innovative doctrine of ideas, insofar as it initiates a materialistic turn of the Idea, can be seen as a prefiguration of this new materialism. According to Kant's elaboration of the Idea, it is nothing but the functioning of a thought which is affected by the “thing of thought” in a given world. The author seeks to develop the “thing of thought” in terms of a point of the real in the Lacanian sense. From this perspective, as a point of the real, the “thing of thought” allows thought to establish itself as thought, at the same time it remains outside thought and irreducible to it.